PENGARUH HARGA DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI TOKO BAMBU WIDIA - Nuryani, Ni Nyoman Juli; Widia Wati, Kadek Diah (Komunitas Manajemen Kompetitif, 2023)
The purpose of this study was to determine the effect of price and product diversity on purchasing decisions at the Bamboo Widia store. The population in this study were all consumers at the Widia Bamboo Shop, both male and femaleIn taking the sampel used in this study were as many 64customer Methods of data collection by using questionnaire techniques and documentation techniques. The type of research used is quantitative research and the data analysis used is multiple linear regression analysis. Data analysis techniques used the SPSS version 22.0 for Windows application. The results showed that price had a positive and significant effect on purchasing decisions with t-count > t-table (3.310 > 1.669) with a significance level of 0.002 <0.05. And product diversity has a positive and significant effect on purchasing decisions at the Widia Bamboo store, t-count > t-table (3.431-1.669) with a significance level of 0.048 <0.05.